Discovering the Economic Impact of Mangrove Conservation: A Comparative Study of Carbon Storage Program in Refining Oil & Gas Company in IndonesiaGas di Indonesia - Bakhtiar Fahmi Fuadi; Wahyu Purwanto; Muh Arif Romadlon (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2025)
Mangroves are extremely important ecosystems for environmental balance and the sustainability of natural resources. In Indonesia, the area of mangrove forests reaches approximately 3.36 million hectares, making it one of the countries with the largest mangrove ecosystems in the world. However, the condition of mangroves in Indonesia faces various threats, such as land conversion for agriculture, illegal logging, and pollution. These factors lead to the loss of ecological functions of mangroves and the potential carbon storage that can be utilized. This study aims to evaluate and compare the economic potential of carbon storage in biodiversity conservation programs for mangroves at PT KPI RU II Sungai Pakning, PT KPI RU V Balikpapan, and PT KPI RU VII Kasim. Mangroves are vital ecosystems that play an important role in carbon sequestration; however, their economic benefits remain underexplored. This research utilizes field data and refers to Indonesian National Standards (SNI) as a guideline for calculating carbon potential at each location. Additionally, we analyze the economic valuation of carbon storage based on the values established in the Carbon pricing by World Bank. The findings reveal significant differences in carbon storage potential, influenced by varying ecosystem conditions and conservation practice